Proposed method for obtaining representative water content and matric suction of a cracked soil - Rahardjo, Harianto (2013)
Water content and matric suction vary significantly throughout a cracked soil during a drying process. Therefore, it is difficult to obtain representative values of water content and matric suction of a cracked soil. In this paper, a method for obtaining representative water content and matric suction of a cracked soil during a drying process is proposed. Two soil specimens were dried from an initially slurried condition until they exhibited cracks. Contours of water content and matric suction were obtained and analyzed following a method to obtain average water content and matric suction of a cracked soil. Average water content and matric suction calculated from the contours were close to those obtained by considering the cracked soil specimen as a single soil element. The good agreement indicates that the average water content and matric suction calculated following the proposed method can be used to represent water content and matric suction values of a cracked soil specimen during a drying process.